Inhibition of Autophagy Prevents Panax Notoginseng Saponins (PNS) Protection on Cardiac Myocytes Against Endoplasmic Reticulum (ER) Stress-Induced Mitochondrial Injury, Ca2+ Homeostasis and Associated Apoptosis - Chen, Jun; Li, Li; Bai, Xueyang; Xiao, Lili; Shangguan, Jiahong; Zhang, Wenjing; Zhang, Xiangqin; Wang, Shen; Liu, Gangqiong (Frontiers in Pharmacology, 2021)
Endoplasmic reticulum (ER) stress is often closely linked to autophagy, hypoxia signaling, mitochondrial biogenesis or reactive oxygen species (ROS) responses. Understanding the interaction between ER stress, mitochondrial function and autophagy is of great importance to provide new mechanisms for the pathology and treatment of cardiovascular diseases. Our previous study has reported that Panax notoginseng saponins (PNS) protection against thapsigargin (TG)-induced ER stress response and associated cell apoptosis in cardiac myocytes is calcium dependent and mediated by ER Ca2+ release through RyR2. However, whether its protection upon ER stress is related to the mitochondrial function and autophagy is still unknown. Here, we investigate the effect of PNS on TG-induced mitochondrial function, ROS accumulation and autophagy. We also assess its effects on Ca2+ homeostasis, ER stress response and associated cell death in the presence of autophagy inhibition. PNS-pretreated primary cultured neonatal rat cardiomyocytes were stimulated with TG to induce ER stress response. Mitochondrial potential (Δψm) was measured by JC-1. The general and mitochondrial ROS were measured by DCFH-DA and MitoSOX Red, respectively. Autophagy was evaluated by immunofluorescence of LC3, and immunoblots of LC3, p62, ATG7 and PINK1, as well as mRFP-GFP-LC3 labeled autophagy influx. SiATG7 transfected H9c2 cells were generated to inhibit the autophagy. Cytosolic and ER Ca2+ dynamics were investigated by calcium imaging. RyR2 oxidation was tested by oxyblot. Cell viability was examined by TUNEL assay. ER stress response and cell apoptosis were detected by immunoblot of BiP, CHOP, Cleaved Caspase-3 and Caspase-12. The results demonstrated that firstly, PNS protects against TG-induced mitochondrial injury and ROS accumulation. Secondly, PNS enhances the autophagy in TG-induced cardiac myocytes. Thirdly, inhibition of autophagy diminishes PNS prevention of TG-induced mitochondrial injury, ROS accumulation and disruption of Ca2+ homeostasis. Finally, inhibition of autophagy abolishes PNS protection on TG-induced ER stress response and associated apoptosis. In summary, PNS protection on ER stress response and associated cell death is related to the mitochondrial injury and ROS elevation, and is mediated by autophagy. These data provide new insights for molecular mechanisms of PNS as a potential therapeutic approach to the management of cardiovascular diseases.